STUDENT-CENTERED APPROACH IN THE SYSTEM OF QUALITY ASSURANCE OF PROFESSIONAL TRAINING OF FUTURE PROFESSIONALS - Iliichuk, Liubomyra (Mountain School of Ukrainian Carpaty, 2022)
In the current conditions of development of higher education in Ukraine the question of realization of the idea of student-centeredness as a necessary component of the system of quality assurance of professional training of future specialists is actualized. The article considers the peculiarities of the student-centered approach as a system-forming principle of the organization of the educational environment of a higher education institution in the conditions of modern educational realities. The main ideas of student-centeredness as an approach to the organization of the educational process in accordance with its components, defined by the Law of Ukraine «On Higher Education» are analyzed and systematized. Procedures for implementing a student-centered approach in accordance with the requirements of Standards and Recommendations for Quality Assurance in the European Higher Education Area are considered. A contextual analysis of student-centeredness as a characteristic feature of higher education is carried out, on the basis of which the social (civilizational), philosophical, social, psychological, pedagogical, managerial and personal aspects of this phenomenon are distinguished. The need to create an educational environment focused on meeting the needs and interests of higher education students has been identified. The role of the idea of student-centeredness in designing the educational environment of a higher education institution is revealed. It was found that the student-centered educational environment is a set of interrelated diverse conditions for the realization of educational needs and interests of students, which includes a system of intellectual and communicative, organizational, educational, informational, technological, material and technical resources. It is emphasized that the implementation of student-centered approach outlines ways to design the educational environment of a modern university, focused on continuous development and self-improvement of future professionals, which is a necessary condition for ensuring the quality of higher education in Ukraine. Keywords: student-centeredness, student-centered approach, educational process, educational environment, professional training, quality of higher education.